Biodiesel production from oleaginous yeast, Cryptococcus sp. by using banana peel as carbon source - Shin Han; Ga-Yeong Kim; Jong-In Han (Energy Reports, 2019)
An oleaginous yeast, Cryptococcus sp., was isolated from a traditional Korean fermented fish and used for bio-oil production with banana peel as a feedstock. Pretreatment of banana peel with 1% sulfuric acid resulted in up to 4.5 g L-1 of glucose (11.2% yield), and 18.1 g L-1 of fructose (45.2% yield). Cryptococcus sp., when grown on the pretreated banana peel, accumulated lipid up to 34.0%; and the lipid had a high degree of mono-saturation, which gives the resulting biodiesel better quality. Lipids were extracted using the pseudo-Fenton reaction based on persulfate as an oxidant, with the extraction efficiency of 91.1%. The data suggest that the new and potent oleaginous yeast, Cryptococcus sp., together with such cheap feedstock as the banana peel, can offer a competitive route for the production of bio-oil
Keywords: 330; Banana peel; Biodiesel; Lipid content; Persulfate; Cryptococcus sp.